3 Ageing of the vascular endothelium: a novel role for CAMKIIδ?. (1st April 1997) - McCluskey, Claire; MacDonald, Margaret; Currie, Susan
Abstract : Calcium/calmodulin–dependent protein kinase II delta (CaMKIIδ) plays a pivotal role in cardiovascular health and disease. Whether CaMKIIδ modulates impaired function in ageing cardiovasculature is unknown. This study investigates cardiac and aortic CaMKIIδ expression and activation in aged rats. Cardiovascular function was assessed in vivo by echocardiography. Reduced fractional shortening (63.2±1.3 vs 50.6±1.9 (%FS), young vs aged (n=12), p<0.01) and increased heart weight:body weight (2.7±0.2 vs 3.6±0.1, young vs aged (n=6), p<0.05) were observed in aged animals suggesting cardiac remodelling. Increased blood flow through the ascending aorta was also observed in aged rats (76.7±3.1 vs 103.4±7.4 (ml/min), young vs. aged (n=12), p<0.05). Parallel investigation of CaMKIIδ in cardiac and aortic tissue revealed increased protein expression (1.03±0.1 vs11.7±0.2, (n=7) p<0.05 (cardiac); 1.1±0.1 vs. 1.3±0.1 (aortic), young vs. aged (n=6) (CaMKIIδ/GAPDH)). Further analysis of aortic tissue showed increased activation of CaMKII with elevations in phosphorylated and oxidised CaMKII (ox-CaMKII) expression (1.2±0.1 vs 1.8±0.2 (n=5) p<0.05; 1.0±0.1 vs 1.3±0.08 (n=5) p<0.05, young vs. aged) as well as increased kinase activity (5.9±1.2 vs 8.2±1.4 (pmolPO4 - inc/min/μg protein) young vs.aged, (n=3)). To explore these novel observations in the vasculature further, endothelial cells from young and aged aortae were isolated. These cells displayed striking phenotypic differences between groups with aged cells displaying clear signs of necrosis. To investigate whether ox-CaMKII may contribute to deterioration of the endothelium in ageing, initial experiments studied young endothelial cells exposed to H2 O2 (10 µM). Reactive oxygen species and ox-CaMKII expression were measured in parallel and a corresponding increase in both parameters occurred following treatment (2.5 × 10 3  vs 4.4 × 10 4 (fluorescence a.u.) control vs treated, (n=3), p<0.01; 1.1±0.2 vs 1.82±0.1 (ox-CaMKII/GAPDH), control vs treated), p<0.001, (n=3)). This work provides new evidence that CaMKIIδ expression and activation are augmented in aged vasculature. Future work will examine CaMKII in aged endothelial cells to provide mechanistic insight into the deterioration of vascular function.